Stem Cell-Derived Exosomes Potential Therapeutic Roles in Cardiovascular Diseases - Selvaraj Jayaraman; Dhanavathy Gnanasampanthapandian; Johnson Rajasingh; Kanagaraj Palaniyandi (Frontiers in Cardiovascular Medicine, 2021)
Owing to myocardial abnormalities, cardiac ailments are considered to be the major cause of morbidity and mortality worldwide. According to a recent study, membranous vesicles that are produced naturally, termed as “exosomes”, have emerged as the potential candidate in the field of cardiac regenerative medicine. A wide spectrum of stem cells has also been investigated in the treatment of cardiovascular diseases (CVD). Exosomes obtained from the stem cells are found to be cardioprotective and offer great hope in the treatment of CVD. The basic nature of exosomes is to deal with the intracellular delivery of both proteins and nucleic acids. This activity of exosomes helps us to rely on them as the attractive pharmaceutical delivery agents. Most importantly, exosomes derived from microRNAs (miRNAs) hold great promise in assessing the risk of CVD, as they serve as notable biomarkers of the disease. Exosomes are small, less immunogenic, and lack toxicity. These nanovesicles harbor immense potential as a therapeutic entity and would provide fruitful benefits if consequential research were focused on their upbringing and development as a useful diagnostic and therapeutic tool in the field of medicine.